THE BENEFITS AND PROBLEMS ENSUING FROM THE INTERNATIONALISATION OF UNIVERSITIES FROM THE POINT OF VIEW OF STUDENTS AND ACADEMIC TEACHERS PARTICIPATING IN THE ERASMUS PROGRAMME - Elżbieta Szymańska (Ekonomia i Prawo, 2014)
The main purpose of the publication is to indicate the benefits from the internationalisation of universities and to diagnose the main obstacles encountered by the participants in this process. The article consists of three basic parts, the introduction and conclusions. The first part, based on the analysis of the literature, presents the publications and studies carried out in the scope of the issues in question which the Author considers most important. The second part presents the major assumptions of the ERASMUS Programme. The third part gives the results of the study, starting with the benefits ensuing from the participation in the programme, both long-term and short-term, while the farther part presents the critical opinions of respondents. The conclusions ending the publication should provide the guidance for the further steps to deepen the process of internationalisation of universities, particularly in the territories of the Member States of the European Union.